2020
DOI: 10.3390/s20174715
|View full text |Cite
|
Sign up to set email alerts
|

A High-Speed Low-Cost VLSI System Capable of On-Chip Online Learning for Dynamic Vision Sensor Data Classification

Abstract: This paper proposes a high-speed low-cost VLSI system capable of on-chip online learning for classifying address-event representation (AER) streams from dynamic vision sensor (DVS) retina chips. The proposed system executes a lightweight statistic algorithm based on simple binary features extracted from AER streams and a Random Ferns classifier to classify these features. The proposed system’s characteristics of multi-level pipelines and parallel processing circuits achieves a high throughput up to 1 spike eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…When introducing feature weighting to calculate the information gain of the current attributes of cloud computing storage data, the relevance of this feature to the classification result can be included [20,21]. e setting of feature weights for each dimension in the system depends on the characteristics of the data stored in cloud computing.…”
Section: Cloud Computing Storage Data Classificationmentioning
confidence: 99%
“…When introducing feature weighting to calculate the information gain of the current attributes of cloud computing storage data, the relevance of this feature to the classification result can be included [20,21]. e setting of feature weights for each dimension in the system depends on the characteristics of the data stored in cloud computing.…”
Section: Cloud Computing Storage Data Classificationmentioning
confidence: 99%
“…For each circle, we search for a continuous arc with higher timestamps than all other pixels on the circle. On the inner circle (blue), the arc length l inner should be within the interval of [ 3 , 6 ], and on the outer circle (yellow), the arc length l outer should be within the interval of [ 4 , 8 ] (see Figure 5 a). Alternatively, the arc length on the inner and outer circle should be within the interval of [ 10 , 13 ] and [ 12 , 16 ], respectively (see Figure 5 b).…”
Section: Methodsmentioning
confidence: 99%
“…Since there are numerous advantages, several recent works [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ] focus on processing the unconventional output of event cameras and unlocking their potentials. In event-based vision, the corner is one of the most fundamental features, and corner event tracking is usually used in many applications, such as target tracking [ 15 , 16 ], 3D Reconstruction [ 17 , 18 ] and motion estimation [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Goh have built an automatic scoring statistical model for Chinese students' English compositions, although the accuracy rate is higher than that of manual scoring [14], but to a certain extent, due to the neglect of the characteristics of text content and deep structure, the number of samples is too small, the source range is small, and it is not representative. [17]. Based on BD personalization and adaptation, Wójcik and Piekarczyk examined the learning process structure, learning process visualization, and learning effect demonstration, and the findings showed that data analysis of students' learning behavior and knowledge mastery could recommend reasonable learning paths and learning resources with appropriate difficulty [18].…”
Section: Introductionmentioning
confidence: 99%